2011
DOI: 10.3233/jad-2011-110125
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Alzheimer's Disease Among Illiterate Elderly: Accuracy Analysis for Multiple Instruments

Abstract: One of the challenges in screening for dementia in developing countries is related to performance differences due to educational and cultural factors. This study evaluated the accuracy of single screening tests as well as combined protocols including the Mini-Mental State Examination (MMSE), Verbal Fluency animal category (VF), Clock Drawing test (CDT), and Pfeffer Functional Activities Questionnaire (PFAQ) to discriminate illiterate elderly with and without Alzheimer's disease (AD) in a clinical sample. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 57 publications
2
56
0
14
Order By: Relevance
“…Muitas pesquisas têm destacado que a escolaridade influencia o desempenho no MEEM (Bertolucci et al, 1994;Brucki, Mansur, Carthery-Goulart, & Nitrini, 2011) e, consequentemente, deve ser considerada ao se estabelecerem pontos de corte. Alerta-se que não somente a quantidade de anos estudados é importante mas também a qualidade do ensino recebido e sua influência sobre o desenvolvimento cognitivo, especialmente na velhice (Aprahamian, Martinelli, Cecato, & Yassuda, 2011) e em países em desenvolvimento, como o Brasil, onde a educação formal é muito heterogênea (Farfel et al, 2013 O segundo componente extraído na ACPOrientação -reuniu os mesmos dez itens agrupados no estudo de Folstein et al (1975). Embora sejam funções importantes a serem avaliadas no contexto da cognição, autores, como Carnero-Pardo (2013), argumentam que valerse de 10 itens para avaliar a orientação em um instrumento com um total de 30 itens pode ser exagero.…”
Section: Procedimentounclassified
“…Muitas pesquisas têm destacado que a escolaridade influencia o desempenho no MEEM (Bertolucci et al, 1994;Brucki, Mansur, Carthery-Goulart, & Nitrini, 2011) e, consequentemente, deve ser considerada ao se estabelecerem pontos de corte. Alerta-se que não somente a quantidade de anos estudados é importante mas também a qualidade do ensino recebido e sua influência sobre o desenvolvimento cognitivo, especialmente na velhice (Aprahamian, Martinelli, Cecato, & Yassuda, 2011) e em países em desenvolvimento, como o Brasil, onde a educação formal é muito heterogênea (Farfel et al, 2013 O segundo componente extraído na ACPOrientação -reuniu os mesmos dez itens agrupados no estudo de Folstein et al (1975). Embora sejam funções importantes a serem avaliadas no contexto da cognição, autores, como Carnero-Pardo (2013), argumentam que valerse de 10 itens para avaliar a orientação em um instrumento com um total de 30 itens pode ser exagero.…”
Section: Procedimentounclassified
“…The Pfeffer Functional Activities Questionnaire seems to be one of the most commonly used tools for functional assessment aiming at the investigation of IADL performance. [7][8][9][10] One study using the Pfeffer scale 7 found an additive effect between functional scores and the Mini Mental State Examination (MMSE) for the diagnosis of AD. The Disability Assessment for Dementia was also adapted for Brazil 11 and seems to be useful for the characterization of functionality in frontotemporal dementia and AD, assessing both BADLs and IADLs as well as leisure activities, although these two groups do not show differences in functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…. and a sample derived from a public primary care unit in Rio de Janeiro" (Lourenço et al, 2008;Aprahamian et al, 2011), further reinforcing the point of view that the matter is not related to the instrument but rather to the specific characteristics of their sample.…”
mentioning
confidence: 99%
“…Bottom line: sample and classification bias have determined the results and conclusions reported by Aprahamian et al (2011), with which we vehemently disagree, i.e. that "the CAMCOG retains high accuracy when used in samples of elderly with limited education".…”
mentioning
confidence: 99%
See 1 more Smart Citation